Analisis Beberapa Jenis Vaksin Covid-19 yang akan Dipakai di Indonesia - MASFUFATUN; NI PUTU MANIK SURYANINGSIH; I MADE DWIKY KARINA JAYA; ALMAIDAH SAFITRI; TEOFILUS DANI PRASETYOADI; JAMES HADIPUTRA SUNARPO (Universitas Hang Tuah, 2022)
At the end of 2019, there was a pandemic that originated in Wuhan, China. This pandemic is known as the corona virus / COVID-19. COVID-19 itself is caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). In Indonesia alone, COVID-19 cases have reached 1.17 million and those who died have reached 31,976 people. From this case, experts are racing to find this COVID-19 vaccine. The COVID-19 vaccine itself is expected to control the spread of the virus in the world. This review article aims to discuss the various types of vaccines that will be used in Indonesia in terms of types, methods of action, efficacy, specificity, sensitivity, dosage, and side effects. The results of the review article show that vaccines are one of the most effective and economical methods. Various studies have been carried out by several experts from around the world to develop a vaccine for COVID-19. Each vaccine used has the same goal, namely to control the spread of the COVID-19 virus which is currently still a pandemic around the world. Based on the results of the review article, it can be concluded that all types of vaccines have their respective advantages and disadvantages. Thus, the community will not feel worried and are more confident in determining what kind of vaccine will be taken.